OPTIMALISASI PENDAPATAN ASLI DAERAH TERHADAP PEMBANGUNAN KOTA SURABAYA - Takaria, Iflaha; Ardini, Lilis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to find out: 1) to find out and to analyze how the optimization the local own sourcerevenue in supporting the development of Surabaya city, 2) to find out and to analyze the problems whichsupport and inhibit Local Own source revenue of Surabaya city. The research method has been done by usingqualitative research, meanwhile the analysis technique data has been done by using descriptive analysis withqualitative approach. It can be concluded from the result of the research that: 1) In 2013-2015 periods, therealization of local own source revenues which has been generated by the Department of Revenue and FinancialManagement to meet the budget. The enhancement of 2013-2015 local own source revenues cannot be separatedfrom the efforts of the local government of Surabaya to support the implementation of local autonomy in whichthe implementation has been conducted by using intensification and extentification. 2) the supporting factors tooptimize the local own source revenue i.e.: the officers should conduct the collection to the Delinquent taxpayer(pick up the ball system). Give warning letter to the delinquent taxpayers. To provide information through theease of paying taxes to the nearest UPTD. To increase the socialization activity to the public. 3) The inhibitingfactors with the optimization of local own source revenue i.e.: the lack of knowledge of the public about thepayment procedure. The department has not been able to determine the punishment yet.4) The level ofdevelopment Surabaya city can be stated quite well, because the local own source revenue has been obtained morethan the budget which has been determined.Keywords: optimization, local own source revenue, local development.